Capacity Building To Inculcate Twelve-Roles Of Medical teacher Using Patient-Safety Theme - Dr Iram Khursheed; Dr Rahila Ali (ziauddin University, 2024)
Background: Teacher's role has evolved from a knowledge-transmitter to that of a learning-facilitator. To professionally develop postgraduate medical/dental trainees-as-teachers (PGTT) considering teaching as one of the exit-level outcomes of their Master's program. A course was conducted on twelve-roles of medical teacher with patient-safety theme. This study was intended to explore the level of PGTT's satisfaction regarding their roles developed in response to their engagement in course activities. Methods: In 2015, a one-week course, 'Fundamentals of Health-Professions-Education (FHPE)' was conducted for 25 PGTT, underpinned with adult learning principles in context of patient-safety theme for the development of twelve-roles of medical teacher. Variety of teaching approaches with formative and summative assessments were done to promote learning-by-doing (Kolb's-theory). A self-administered cross-sectional questionnaire on a 5-point Likert scale was used with 29 questions on role of course facilitators, Course plan & conduct and Development of their own teaching skills. Satisfaction-level was expressed in the form of percentages. Results: All 25 PGTT responded on three major domains of the questionnaire. All (100%) agreed on the effectiveness of the roles of course facilitators and the course plan & conduct. Majority (96%) of them showed agreement on the improvement of their teaching skills developed during this course. Conclusion: The FHPE-course was found as a worthwhile opportunity for PGTT in acquiring the desired outcomes under-supervision and with respect to its future implications in their respective settings. Building capacity for scholarship of teaching & learning is a way forward to successful academic achievements. Key Words: Roles of medical teacher, patient-safety, post graduate students as teachers, capacity building, health professions education.